Landsbyen Tvååker og Sorø Klosters ejendom dér - Hørby, Kai; Olsen, Rikke Agnete (Hikuin, 2004)
The village of Tvååker and the property of the cistercian monastry at Sory By Kai Hørby and Rikke Agnete Olsen A new transcription, reading and translation of the pages concerning the property in Halland in the book of donations of the monastery of Sorø. The new reading combined with a detailed survey of maps of the area and a thorough visit to it has made it possible to suggest the size of the property.